Attribute-based secure messaging in the public cloud - POH, Zhi Yuan (Institutional Knowledge at Singapore Management University, 2017)
Messaging systems operating within the public cloud are gaining popularity. To protect message confidentiality from the public cloud including the public messaging servers, we propose to encrypt messages in messaging systems using Attribute-Based Encryption (ABE). ABE is an one-to-many public key encryption system in which data are encrypted with access policies and only users with attributes that satisfy the access policies can decrypt the ciphertexts, and hence is considered as a promising solution for realizing expressive and fine-grained access control of encrypted data in public servers. Our proposed system, called Attribute-Based Secure Messaging System with Outsourced Decryption (ABSM-OD), has three key features: enabling expressive and fine-grained access control of encrypted messages by users, supporting outsourced decryption to the cloud while without compromising confidentiality of decrypted messages, and allowing server-aided revocation to provide effective and instant user revocations.